(untitled) - Shortland, Michael (Harlow, England, 1991)
An aid for scientists in effective communication with th e general population of any of their given research/subject areas. Covers writing skills (for magazines, newspapers, even preparing a book proposal), speaking, and print and broadcast media
Phương pháp nghiên cứu khoa học môi trường
Keywords: Communication in science,Truyền đạt thông tin trong thư viện